Pengelolaan Penyewaan Auditorium Universitas Nasional dengan Metode Rational Unified Process - Muklis Haryono; Iskandar Fitri; Nurhayati Nurhayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The Auditorium of the National University is one of the assets and facilities at the National University which is managed by the Public Administration Unit (BAU). Usually, the public rents the auditorium for various purposes such as for seminars, weddings, training, and so on. However, currently, the auditorium rental process is still manual, where tenants must come directly to the BAU unit of the National University to obtain building information and schedule certainty. This makes tenants need more time if they want to rent. This study develops a web-based application for the Management of the National University Auditorium Rental with the Rational Unified Process (RUP) method as a solution to these problems. The development will highlight the RUP model and utilizing the Unified Modeling Language (UML) tool for modeling and using the PHP language for construction. The result of this research is the availability of a rental management application that makes tenants easier to rent the auditorium and makes the BAU unit easier to manage the auditorium rental. The results of application testing using the black box method show that all application functions are running well. In addition, testing using the User Acceleration Test (UAT) application easy to use 92%, asy menu display 88,8% and software features 86,4%.